(E)-4-((4-Bromobenzylidene) Amino)-N-(Pyrimidin-2-yl) Benzenesulfonamide from 4-Bromobenzaldehyde and Sulfadiazine, Synthesis, Spectral (FTIR, UV–Vis), Computational (DFT, HOMO–LUMO, MEP, NBO, NPA, ELF, LOL, RDG) and Molecular Docking Studies. (26th November 2022) - Sowrirajan, S.; Elangovan, N.; Ajithkumar, G.; Manoj, K. P.
Abstract: (E)-4-((4-bromobenzylidene) amino)-N-(pyrimidin-2-yl) benzenesulfonamide were synthesized with condensation of 4-bromobenzaldehyde and sulfadiazine (4BRDA). This compound characterized with FTIR and Electronic spectra in experimental part. The calculated part used for DFT mode and B3LYP with 6311++G(d, p) basic set. IR designed with B3LYP/6311++G(d, p) basic set, and UV–Vis spectra computed with TD-DFT (time-dependent density functional theory) mode with same basic set level, with IEFPCM solvation model and dimethyl sulfoxide used for solvent. ADME properties considered with Swiss ADME online tools. Molecular docking calculation calculated with patch-dock online server. The Multiwfn software used for compute the ELF, RDG and LOL.